1994
DOI: 10.1002/eji.1830240950
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide specifically induces human IgA1 and IgA2 production

Abstract: The effects of vasoactive intestinal peptide (VIP) on human IgA1 and IgA2 production were studied. In unfractionated small resting B cells stimulated with anti-CD40 monoclonal antibody (mAb), VIP induced IgA1 and IgA2 production without affecting the production of IgG1, IgG2, IgG3, IgG4, IgM, or IgE. When small B cells were separated into sIgA1+, sIgA2+, sIgA1- and sIgA2- B cells, anti-CD40 mAb plus VIP induced IgA1 and IgA2 production by surface IgA1- (sIgA1-) and sIgA2- B cells, respectively, while having no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The data of neutralization test at the protein level are in agreement with previous findings of IgA production from IgA Ϫ B cells (15).…”
Section: Vip Induced Iga Production By Igdsupporting
confidence: 92%
See 2 more Smart Citations
“…The data of neutralization test at the protein level are in agreement with previous findings of IgA production from IgA Ϫ B cells (15).…”
Section: Vip Induced Iga Production By Igdsupporting
confidence: 92%
“…Total mRNA was obtained from cultured B cells (1 ϫ 10 7 cells) using Trizol reagent (Life Technologies, Gaithersburg, MD) (21) and then digested with DNase I (Sigma) to remove contaminating DNA. 2 g of total RNA was reverse-transcribed to cDNA using oligo (dT) 15 (Boehringer-Mannheim Co., Indianapolis, IN) as primer and mouse Moloney leukemia virus reverse transcriptase (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Representing the most abundant Ig isotype in humans, an important role of IgA in host protection has long been postulated (2,38). The isotype switch to IgA and its secretion can be induced by TGF-␤-dependent and TGF-␤-independent mechanisms (11)(12)(13)(14)(15)(16)(17)(18)(19). Making use of a mouse model lacking T␤R selectively in B cells (24), the present study shows that the efficient production of Ag-specific mucosal IgA is driven by T␤R signaling (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ has also attracted significant attention, since in vitro tests showed that TGF-␤ stimulates the isotype switch to IgA, as well as IgA secretion by LPS-stimulated mIgA Ϫ B cells from Peyer's patches and spleen (11)(12)(13)(14)(15). Remarkably, a TGF-␤-independent mechanism of isotype switch to IgA has been proposed in ϩ murine B cells stimulated with LPS and all-trans-retinoic acid (16,17), as well as in human mIgA1/2 Ϫ B cells coincubated with vasoactive intestinal peptide and anti-CD40 mAb (18,19).…”
mentioning
confidence: 99%